Gratings in novel fibre geometry for applications in shape sensing - Kalli, Kyriacos; Dobb, Helen L.; Allsop, Thomas P.; Webb, David (My University, 2004)
A long period grating (LPG) fabricated in progressive three-layered (PTL) fibre is described. The grating with a period of 391μm, had dual attenuation bands associated with a particular cladding mode. The dual attenuation bands have been experimentally characterised for their spectral sensitivity to bending, which resulted in the highest sensitivity to bending seen for this particular fibre and temperature. The spectral characteristics of the fibre have been modelled giving good agreement to the experimental data as well as showing that the attenuation bands are both associated with the second order HE/EH2,n cladding mode.
Keywords: Mathematical models; Optical fibers; Refractive index; Diffraction gratings